PEDAGOGICAL TECHNOLOGIES IN ACCORDANCE WITH THE SPECIFIC CHARACTERISTICS OF TEACHING AND THEIR DESCRIPTION (American Journal of Pedagogical and Educational Research, 2023)
This article provides information about pedagogical technologies and their description that are in accordance with the specific characteristics of teaching.